INVESTIGATION OF ANTIMICROBIAL TREATMENT OF TEXTILE MATERIALS ON THE EFFECTIVENESS OF INHIBITION OF BACTERIAL CONTAMINATION FROM THE ENVIRONMENT - HOROKHOV, Ihor; KULISH, Irina; ASAULYUK, Tatyana; SARIBYEKOVA, Yulia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The purpose of the work is to develop an antimicrobial composition and study the quality of antimicrobial treatment of cotton textile materials. An aqueous solution of polyhexamethylene guanidine chloride was used as an object of study as an effective, safe antimicrobial agent. To increase the stability of the treatment to washing, additives of glycidyl ethers capable of crosslinking reaction, with epoxy groups of different functionality and mass fraction were studied. The treatment of cotton fabric was carried out by impregnation with an aqueous solution of polyhexamethylene guanidine chloride and glycidyl ethers in a finishing bath, followed by drying and curing. Checking the antimicrobial effect of cotton fabric was carried out by the settle plate method by analyzing the diffusion of the fabric disc on agar after treatment with an antimicrobial composition and after washing. The paper presents the results of a study of the quality of cotton fabric treatment from the use of polyhexamethylene guanidine chloride and various glycidyl ethers in the antimicrobial composition to increase the resistance to washing. The efficiency of inhibition of bacterial contamination from the environment of fabric samples treated with the antimicrobial composition was established. The results of the experiment showed that almost all fabric samples modified with polyhexamethylene guanidine chloride and glycidyl ethers are characterized by a pronounced zone of inhibition of microflora seeded from the air, but a composition containing butyl cellosolve monoglycidyl ether with a mass fraction of epoxy groups of 16.0 – 20.0% has a greater resistance to washing. It has been proven that the introduction of butyl cellosolve monoglycidyl ether with a mass fraction of epoxy groups of 16.0 – 20.0% into a finishing composition based on polyhexamethylene guanidine chloride makes it possible to provide an antimicrobial effect of a textile material and increase the resistance of the antimicrobial effect to washing. The obtained results of the experiment are of practical importance for the development of new finishing compositions in order to impart antimicrobial properties to textile materials.